Analysis of the Coal and Gas Outburst Mechanism from the Perspective of Tectonic Movement. (5th July 2021) - Tu, Qingyi; Cheng, Yuanping; Xue, Sheng; Ren, Ting; Cheng, Xiang
Abstract : Coal and gas outburst is the extreme instability caused by stress, gas, and coal. In this review article, dominant factors and inducing factors of outburst were summarized; geologic features of typical outburst cases and the effects of tectonic movement on outbursts were analyzed; the outburst stages with considerations to geologic factors were divided. It was found that inducing factors, including buried depth, tectonic movement, gas composition, coal seam conditions, overlying/underlying rock conditions, and mining mode, control the outburst by influencing the dominant factors (stress, gas, and coal). Among them, tectonic movement is the key of outburst. Influenced by tectonic movement, the primary structure of coals is damaged/pulverized due to the tectonic stress and unique tectonic mode, resulting in the formation of tectonic coals. When external dynamic factors are changed, tectonic coals are crucial to outburst control for its evolution of porous structure as well as the unique mechanical behaviors and gas flowing responses. Besides, the preparation stage of outburst includes the tectonic process and mining process. The former one refers to the restructuring process of the original coal-bearing strata by tectonic movement, while the mining process is the prerequisite of outburst and it refers to the disturbance of human mining activities to the initial coal seams. It is suggested that more work is required on geological factors of outburst, and a few research areas are proposed for future research.